Application of dynamic diffusion theory in foreign direct investment of Taiwan IC industry in China. (14th December 2009) - Tsai, Bi-Huei
This study applies dynamic diffusion theory to forecast Foreign Direct Investments (FDIs) of Taiwan IC industry into China. We compare the FDI external and internal influence factors among IC design, packaging and testing industries. The internal impact is stronger for IC packaging and testing firms than for IC design ones, revealing the profound imitating inclination of IC packaging and testing industry. The potential FDI amount is estimated to be much greater for IC packaging and testing industry. Consistent with product life cycle theory, Taiwan transfers low-end IC packaging and testing manufactory toward China where the labour wages are much lower.